Community based education development patterns in Nurul Iman Islamic Boarding School Jambi Province - Liriwati, Fahrina Yustiasari; Zulhimma, Zulhimma; Mulyadi, Mulyadi; Nasrullah, Nasrullah (International research journal of management, IT and social sciences, 2020)
This research was conducted with the aim of knowing the pattern of community based education development in the Nurul Iman Islamic boarding school in Jambi. This research is a descriptive study using a qualitative approach with case study research design in the sense that research is focused on just one phenomenon that is chosen and wants to be understood in depth. This research was conducted directly by using field notes and cameras for documentation. Data collection is done by the method of in depth interviews and observations. The results of the research from the Community Based Education Development Pattern in the Nurul Iman Islamic boarding school in Jambi can be divided into two important components, namely: through the first component is the Teaching Pattern with Community Spiritual Education and Community Work Education and the second component is the Islamic Leadership Pattern. Participation Community members in the Nurul Iman Islamic Boarding School and Stakeholders in Educational Development have felt well in the form of thought participation, labor participation, property participation, skills participation or proficiency and social participation.